Engineering a Biocompatible Scaffold with Either Micrometre or Nanometre Scale Surface Topography for Promoting Protein Adsorption and Cellular Response. (27th February 2013) - Le, Xuan; Poinern, Gérrard Eddy Jai; Ali, Nurshahidah; Berry, Cassandra M.; Fawcett, Derek
Abstract : Surface topographical features on biomaterials, both at the submicrometre and nanometre scales, are known to influence the physicochemical interactions between biological processes involving proteins and cells. The nanometre-structured surface features tend to resemble the extracellular matrix, the natural environment in which cells live, communicate, and work together. It is believed that by engineering a well-defined nanometre scale surface topography, it should be possible to induce appropriate surface signals that can be used to manipulate cell function in a similar manner to the extracellular matrix. Therefore, there is a need to investigate, understand, and ultimately have the ability to produce tailor-made nanometre scale surface topographies with suitable surface chemistry to promote favourable biological interactions similar to those of the extracellular matrix. Recent advances in nanoscience and nanotechnology have produced many new nanomaterials and numerous manufacturing techniques that have the potential to significantly improve several fields such as biological sensing, cell culture technology, surgical implants, and medical devices. For these fields to progress, there is a definite need to develop a detailed understanding of the interaction between biological systems and fabricated surface structures at both the micrometre and nanometre scales.